2016
DOI: 10.15184/aqy.2016.91
|View full text |Cite
|
Sign up to set email alerts
|

Combustion at the late Early Pleistocene site of Cueva Negra del Estrecho del Río Quípar (Murcia, Spain)

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…That there is, from 400 ka onward, such a marked, geographically widely distributed pattern of regular fire use ( 24 ) does not imply that hominins might not have used fire before 400 ka. Indeed, it has been suggested that traces of anthropogenic fire might be around 0.8 Ma old in Spain ( 47 , 48 ) and Israel ( 49 , 50 ), 1 Ma old in South Africa ( 51 54 ), or even older in East Africa ( 19 , 55 57 ). Furthermore, based on paleoanthropological evidence for anatomic changes, Wrangham and Carmody ( 58 ) have argued that fire was first used by Homo erectus 1.8 Ma ago.…”
Section: The Spatiotemporal Pattern Of Fire Usementioning
confidence: 99%
“…That there is, from 400 ka onward, such a marked, geographically widely distributed pattern of regular fire use ( 24 ) does not imply that hominins might not have used fire before 400 ka. Indeed, it has been suggested that traces of anthropogenic fire might be around 0.8 Ma old in Spain ( 47 , 48 ) and Israel ( 49 , 50 ), 1 Ma old in South Africa ( 51 54 ), or even older in East Africa ( 19 , 55 57 ). Furthermore, based on paleoanthropological evidence for anatomic changes, Wrangham and Carmody ( 58 ) have argued that fire was first used by Homo erectus 1.8 Ma ago.…”
Section: The Spatiotemporal Pattern Of Fire Usementioning
confidence: 99%
“…This includes dispersed charcoal fragments in caves, including those found in level TE19 G at the Sima del Elefante site (Atapuerca, Spain) 21 , or in open-air sites, such as Boxgrove (UK) 22 . Thermally altered materials, such as bone and chert, have also been found in Cueva Negra del Rio Quípar in Spain 23,24 , among other sites 9 . However, the anthropogenic nature of these remains is controversial because it cannot be excluded that they are in secondary position and originate in wildfires outside the cave 25 .…”
mentioning
confidence: 95%
“…Eating together is one of the most commonly shared practices among human beings, both across space and time. The remains of food around traces of fireplaces, the oldest fireplaces discovered as far back as about 800,000 years ago [ 1 ], reveal for how long we can confidently say that human beings have been sharing food. In fact, food sharing is described in evolutionary anthropology as a fundamental part of human evolution, as a means of reciprocal cooperation, which we share with other primates [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%